Nitric oxide: does it have an etiological role in pre-eclampsia? - Rajagopal, M; Moodley, J; Chetty, R (2003)
AIM: To determine evidence of nitric oxide (NO) in decidual biopsies and fetal membranes of preeclamptic women. BACKGROUND: Nitric oxide, a potent vasodilator, has been postulated to have a role in the etiology of preeclampsia. Investigations in peripheral blood have led to conflicting results. We therefore decided to study whether immunohistochemically detectable nitric oxide is produced in the decidua and within the fetal membranes. METHODS: Forty-two pregnant women at 28 weeks gestation or more were enrolled. Twenty were normotensive and 22 had preeclampsia. Women with chronic hypertension, diabetes and multiple pregnancies were excluded. Maternal blood samples prior to cesarean section (CS), decidual biopsies during CS, and fetal membrane specimens were obtained. The tissue specimens were fixed immediately (after delivery of the baby and placenta) in formalin, washed, and embedded in paraffin. Immunohistochemical staining for nitric oxide synthases (NOS) I, II, III was performed and reviewed in conjunction with routine hematoxylin and eosin sections, using light microscopy. RESULTS: There was no statistically significant difference in the level of immunostaining of nitric oxide synthases in both normotensive and hypertensive patients. DISCUSSION: The severity of blood pressure did not influence expression of nitric oxide synthases.